Social Support and Job Stress in Female Police Officers: Full mediation from Work-Life Balance - Buhari, Imelda Permila; Suryanto (Sekolah Tinggi Ilmu Kepolisian, 2025)
Women's dual roles as workers and housewives render them particularly susceptible to work stress. The objective of this study was to ascertain the role of work-life balance in female police officers. The research hypothesis posits that work-life balance plays a mediating role in the relationship between social support and work stress among female police officers. The present study employed a quantitative survey-cross-sectional design. The data were collected using a questionnaire disseminated via Google Form and subsequently distributed through social media with a purposive sampling technique. A total of 190 female police officers participated in the operation. The instruments employed in this study included the Revised-Multidimensional Scale of Perceived Social Support, the Work-Life Balance Scale, and the Job Stress Scale. The data analysis technique employed utilized the PROCESS macro model 4 mediation analysis by Hayes. The findings indicated that work-life balance effectively mediated the relationship between social support and work stress. This finding underscores the significance of social support, defined as the presence of conditions that promote effective work-life balance, in mitigating work stress among female police officers. The limitations and recommendations are delineated in the section's conclusion.